Limiares auditivos eletrofisiológicos com os estímulos NB CE-Chirp® LS e NB iChirp no público infantil - Mattiazzi, Ângela Leusin (2022)
The present research described reference values for the electrophysiological thresholds of the frequency specific Auditory Brainstem Response (ABR) with the NB CE-Chirp® LS and NB iChirp stimuli in hearing infants and compared the minimum level of responses, latency and amplitude of both stimuli (Article 1). Also, it sought to analyze the correlation between the electrophysiological thresholds, with the same stimuli, and the behavioral ones of children with hearing loss (Article 2). The time of testing for both stimuli were compared. 74 hearing infants and 21 hearing impaired children participated in this study. The frequencies investigated were 500Hz, 1000Hz, 2000Hz and 4000Hz, by air conduction with the NB CE-Chirp® LS stimulus in the Eclipse equipment, and with the NB iChirp in the SmartEP. The hearing impaired children were also submitted to behavioral auditory assessment. The electrophysiological thresholds for the hearing infants were obtained in the same session, in natural sleep, and in most participants, unilaterally. As for the hearing impaired children, the research was performed in both ears, in half of the sample at 500Hz and 2000Hz and at 1000Hz and 4000hz in the rest, this choice was made by draw. For both groups, the minimum levels of response were researched, i.e. the lower intensity at which the wave V was visualized, and the time of testing was clocked. All exams were evaluated by judges with experience in ABR, after being tabulated and statistically analyzed. In regard to the thresholds of hearing infants, the minimum levels of response and the latency at 500Hz and 1000Hz showed a statistically significant difference between the stimuli, with lower thresholds and higher latencies for the NB iChirp. Higher amplitudes were obtained with the NB iChirp stimulus. The average time of testing for the threshold investigation at the four frequencies was 40 minutes for each ear. For children with hearing loss, there was a strong correlation between the two stimuli and also between electrophysiological and behavioral thresholds at the frequencies of 1000Hz, 2000Hz and 4000Hz. The mean differences between the electrophysiological and behavioral thresholds were below 6dBnHL and the time of testing was similar between the equipment. From these data, the study made it possible to estimate reference values for the electrophysiological thresholds with the NB CE-Chirp® LS and NB iChirp for hearing infants and found that with the NB iChirp the latency of responses is influenced by frequency and that this stimulus provides better amplitudes when compared to the NB CE-Chirp® LS. Additionally, it was possible to evidence that the NB CE-Chirp® LS and the NB iChirp similarly measure the electrophysiological thresholds of children with hearing loss and accurately estimate the behavioral auditory thresholds of this population. There was no difference in the time of testing between the stimuli for both normal-hearing infants and hearing impaired children.